Numerical investigation of quench event in the innermost pair of the KSTAR central solenoids. (September 2020) - Oh, Dong Keun; Oh, Sangjun; Chu, Yong
Highlights: The numerical stability is improved for the upgraded SuperMagnet model. The unique quench of the KSTAR magnet is clarified by the upgraded model. The possibility of precise modeling is proven for the quench event in CICC networks. Abstract: In 2011, the KSTAR tokamak underwent a real quench, and it is recorded as the unique event of ramp-down by quench detection in the magnet operations. Upon efforts to survey the measured data, the current profile in the event was identified as a possible quench-generating operation for the first time when a minimalistic (0-D thermal) model assessed risk of the given current profile. However, any usable simulator on the practical thermohydraulic condition has not been established because of limited performance of the latest modeling tools. Recently, mitigating the trouble of numerical instability, the thermohydraulic simulator is significantly improved owing to our effort to overcome the drawback of the generic coupled simulation model. Thus, our SuperMagnet model of the quench event is successfully upgraded to have acceptable numerical performance. As a result, its numerical outputs are discussed as a post-event investigation of quench generating scenario. Based on the simulation work, we describe actual states of the magnet under the flow driven by the quench, whose detail cannot be discovered only looking into the experimental data. As a result, some tangible interpretations are introduced, in particular, on the conductor performance, and physical states of the magnet under the quench.